Abelian varieties, theta functions, and the Fourier transform - Polishchuk, Alexander, 1971- (Cambridge tracts in mathematics, 2003)
The aim of this book is to present a modern treatment of the theory of theta functions in the context of algebraic geometry. The novelty of its approach lies in the systematic use of the Fourier-Mukai transform.